Preoperative physical performance as predictor of postoperative outcomes in patients aged 65 and older scheduled for major abdominal cancer surgery: A systematic review. Issue 3 (March 2022) - Argillander, T.E.; Heil, T.C.; Melis, R.J.F.; van Duijvendijk, P.; Klaase, J.M.; van Munster, B.C.
Abstract: Background: Abdominal cancer surgery is associated with considerable morbidity in older patients. Assessment of preoperative physical status is therefore essential. The aim of this review was to describe and compare the objective physical tests that are currently used in abdominal cancer surgery in the older patient population with regard to postoperative outcomes. Methods: Medline, Embase, CINAHL and Web of Science were searched until 31 December 2020. Non-interventional cohort studies were eligible if they included patients ≥65 years undergoing abdominal cancer surgery, reported results on objective preoperative physical assessment such as Cardiopulmonary Exercise Testing (CPET), field walk tests or muscle strength, and on postoperative outcomes. Results: 23 publications were included (10 CPET, 13 non-CPET including Timed Up & Go, grip strength, 6-minute walking test (6MWT) and incremental shuttle walk test (ISWT)). Meta-analysis was precluded due to heterogeneity between study cohorts, different cut-off points, and inconsistent reporting of outcomes. In CPET studies, ventilatory anaerobic threshold and minute ventilation/carbon dioxide production gradient were associated with adverse outcomes. ISWT and 6MWT predicted outcomes in two studies. Tests addressing muscle strength and function were of limited value. No study compared different physical tests. Discussion: CPET has the ability to predict adverse postoperative outcomes, but it is time-consuming and requires expert assessment. ISWT or 6MWT might be a feasible alternative to estimate aerobic capacity. Muscle strength and function tests currently have limited value in risk prediction. Future research should compare the predictive value of different physical instruments with regard to postoperative outcomes in older surgical patients.